Developing talent management for organizational excellence: a case study at secretariat general of ministry of energy and mineral resources - Rahmani Sugiharto, Reni; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2018)
Abstract – In achieving organizational excellence in accordance with the mandate of the President for the people of Indonesia which prioritizes Bureaucratic Reform in the national development goals, it is time for the Secretariat General of the MEMR to focus on talent management to be implemented in the Ministry of Energy and Mineral Resources thoroughly in the future. In order to initialize the application of talent management in service to the general public, the author in this final project examines Strengths, Weaknesses, Opportunities, and Threats of Human Resource Management at the MEMR using SWOT Analysis and Talent Management strategy to answer the research objective, that is to propose Talent Management model that are in accordance with the vision and mission of the Ministry of Energy and Mineral Resources. To achieve the purpose of this writing, there are 3 (three) questions in the final project that are attempted to be analyzed in this final project, they are: (i) what kind of talent management strategy has been applied specifically to the position of Administrator and Supervisor at the Ministry of Energy and Mineral Resources, (ii) what are the strengths, weaknesses, opportunities and threats of the strategy in the position of Administrator and Supervisor at the Ministry of Energy and Mineral Resources, and (iii) what solutions and recommendations that the Ministry of Energy and Mineral Resources could do to minimize threats in implementing talent management strategies in the future will come. In this final project, the author uses qualitative research methods namely literature review and interview. From various sources (books, journals, expert resource persons, applicable government regulations and interviews), the author tries to examine each of the sources of information in detail to obtain the purpose of writing this final project, namely to present examples of Talent Management models that are appropriate to the vision and mission of the Ministry of Energy and Mineral Resources and answer the first question of this final project. SWOT analysis is also used by the author to answer the second question of this final project. While to answer the third question of this final project, the author uses an analysis of 8 (eight) Management Change Steps initiated by J.P. Kotter. Based on the research method and process of analysis in this final project, results are obtained such as (i) talent management strategies have not yet been implemented in the Ministry of Energy and Mineral Resources, although most of the selection process to employee retirement still uses HR Management strategies. This strategy focuses on all employees in the organization, not on "key employees" or "talents" who can be defined as people who routinely exceed expectations while showing correct and appropriate behavior in this research approach, (ii) there are several strengths, weaknesses, opportunities and threats found in HR development strategies at the Ministry of Energy and Mineral Resources. Its strength is selection based on performance measurement data (SKP), integrity (user evaluation), SIPEG application data for daily attendance, Meeting Forum or Baperjakat which is always under the leadership of the Secretary General and an assessment process organized by third parties. The disadvantage is the selection of filling positions that are done according to needs without planning, the comparison between candidates and vacant positions is very large, the process is done in a hurry and the process of harmonization of time that takes a short time in aligning the schedule of Echelon II leaders in organizing Baperjakat. The opportunity to develop talent management patterns at the Ministry of Energy and Mineral Resources is derived from the framework of good governance, workforce growth, organizational reputation, people development, inventory of future leaders, and statements and support of the Deputy Minister of Energy and Mineral Resources regarding Human Capital strategies in this agency. The last is that threats such as apathetic work and the slow achievement of long-term organizational strategies in this organization are a challenge in the development of talent management strategies, and (iii) to minimize these threats, the Ministry of Energy and Mineral Resources needs to start implementing Talent Management in the management of HR development. Focusing on "key-staff" and "talent", talent management strategies can help organizations overcome talent needs to fill strategic vacant positions in the organization.Keywords: human capital, organizational excellent, people development, talent, talent management, talent pool